Vocal divergence between two disjunct populations of Giant Antshrike (Batara cinerea) is related to environmental conditions - Sementili-Cardoso, Guilherme [UNESP]; Donatelli, Reginaldo Jose [UNESP] (Wiley-Blackwell, 2019)
Variation in the avian vocal signals emitted may have a significant impact on species evolution. Vocal divergence in suboscine species like Giant Antshrike (Batara cinerea) may be associated with selective adaptation, since learning has little influence on vocal development and variation in acoustic structure cannot be attributed to learning deviation. Consequently, tracheophone suboscine species are ideal subjects to explore vocal variation, since cultural evolution does not seem to influence vocal variation in this group. Environmental conditions may determine the selection of vocal features because acoustic transmission could be attenuated under certain conditions of temperature, humidity and vegetation cover. Here, we examined vocalizations of Giant Antshrike and assessed possible acoustic variations between two disjunct groups (Andean and Atlantic), correlating the differences to the environmental structure. Univariate and multivariate analysis show temporal and spectral differences between both groups. Andean individuals produce vocalizations with longer duration, faster trill rates, shorter syllable duration and higher frequencies. Environmental features are different between the two populations, and they are correlated to the acoustic structure of vocalizations. Temporal variations arise directly from climatic influence, while spectral divergence could be a secondary effect of morphological adaptation to habitat structure.
Keywords: acoustic adaptation; birdsong; environmental selection; suboscine; vocal variation